Answer:
m=x+6
Step-by-step explanation:
Let's solve for m.
mx=x(x+6)
Step 1: Divide both sides by x.
2x/x= x²+6x/x
m=x+6
Hope this helps :)
PLS BRAINLIEST
Answer:
minimum value of function is
.
Step-by-step explanation:
Given function represents a parabola.
Now, here coefficient of
is positive , so the parabola will be facing upwards and thus the function will be having a minimum.
Now, as we know that minimum value of a parabolic function occurs at
x =
.
Where , b represents the coefficient of x and a represents the coefficient of
.
here, a = 2 , b = -6
Thus
=
=
So, at x =
minimum value will occur and which equals
y = 2×
-
+ 9 =
.
Thus , minimum value of function is
.
In case A, as the error would be a difference of 1, the assumption could be mantained, but in case B the difference will be bigger, showing that the ratio is not 3:1 but 4:1.
<h3><u>Ratios</u></h3>
Given that a preliminary study was carried out to test the hypothesis that the ratio of white to dark herons on the island was 3:1, but A) a small census found 16 white morphs and 4 dark, to determine if the assumption of a 3 :1 ratio could be rejected, and B) to determine the same question if the census were larger with 160 white morphs and 40 dark, the following calculations must be made:
A)
- 3 + 1 = 4
- 16 + 4 = 20
- 4 = 20
- 3 = X
- 60 / 4 = X
- 15 = X
- Therefore, as the error would be a difference of 1, the assumption could be mantained.
B)
- 3 + 1 = 4
- 160 + 40 = 200
- 150 = 3:1
- In this case, the difference will be bigger, showing that the ratio is not 3:1 but 4:1.
Learn more about ratios in brainly.com/question/1504221
Answer:
78.95cm^2
Step-by-step explanation:
The equation for a cylinder is rπ^2 · h
2π²·4≈78.95
Answer:
The value of x is reciprocal of the difference of a and b.
Step-by-step explanation:
We are given the equation, ![ax=bx+1](https://tex.z-dn.net/?f=ax%3Dbx%2B1)
On simplifying, we get,
![ax=bx+1](https://tex.z-dn.net/?f=ax%3Dbx%2B1)
i.e. ![ax-bx=1](https://tex.z-dn.net/?f=ax-bx%3D1)
i.e. ![(a-b)x=1](https://tex.z-dn.net/?f=%28a-b%29x%3D1)
i.e. ![x=\frac{1}{a-b}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B1%7D%7Ba-b%7D)
So, we get,
The value of x is
.
That is, the value of x is reciprocal of the difference of a and b.